Validating and normalizing passion questionnaire among athletes - Fatemeh Jafari Siavashani; Reza Nikbakhs; Ali Mohammad Safania (مجله علوم روانشناختی, 2018)
Background: Of the main elements that may be considered the most important internal or external factor for an athlete in achieving his objective and manifesting various behaviors is motivation and passion. Aims: The aim of present research is to normalize passion questionnaire in athletic society. Method: Statistical population of this study includes athletes in each of futsal, volleyball, basketball, water polo leagues. In order to review data, exploratory and confirmatory factor analyses and for data gathering Vallerand passion (2003) questionnaire with three elements of obsessive passion (6 questions), harmonious passion (6 questions) and passion measure (5 questions) were used. Overall, 250 questionnaires were distributed and at the end, 200 accurate questionnaire were analyzed. In order to normalize questionnaires confirmatory and exploratory factor analyses and LISREL software were used. Results: Results obtained confirmed the reliability of questionnaire. Research results showed that present questionnaire is an appropriate instrument for measuring passion with emphasis on the importance of sport status among athletes. Furthermore, research final model showed that harmonious passion is first priority and obsessive passion is considered as second priority in sport.Conclusions: It is suggested that researchers in their future research utilize this questionnaire in various and larger samples